2016
DOI: 10.21873/anticanres.11039
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of KRAS Mutation in Rectal Cancer Using MRI

Abstract: KRAS mutations were associated with N stage, a polypoid pattern, axial tumor length, and the ratio of the axial to the longitudinal dimensions of the tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 15 publications
3
41
2
Order By: Relevance
“…More robust machine learning classifiers have also identified radiomic signatures capable of predicting KRAS (AUC = 0.829), NRAS (AUC = 0.686), and BRAF mutations (AUC = 0.857) in a cohort of 117 CRC patients [171]. Magnetic resonance imaging has also been analyzed where it was observed that, in rectal cancer, KRAS mutations were associated with N stage, axial tumor length, and a polypoid pattern [172]. DCE MR parameters, however, were not associated with either KRAS mutation or microsatellite instability, an important prognostic and predictive biomarker for colorectal cancer [173].…”
Section: Colorectal Carcinomamentioning
confidence: 99%
“…More robust machine learning classifiers have also identified radiomic signatures capable of predicting KRAS (AUC = 0.829), NRAS (AUC = 0.686), and BRAF mutations (AUC = 0.857) in a cohort of 117 CRC patients [171]. Magnetic resonance imaging has also been analyzed where it was observed that, in rectal cancer, KRAS mutations were associated with N stage, axial tumor length, and a polypoid pattern [172]. DCE MR parameters, however, were not associated with either KRAS mutation or microsatellite instability, an important prognostic and predictive biomarker for colorectal cancer [173].…”
Section: Colorectal Carcinomamentioning
confidence: 99%
“…From1972 to 2005, the rates of rectal cancer have increased from 7.68 and 6.51 to 11.45 and 8.28 per 100,000 in males and females, respectively [4]. Nevertheless, with the improvement of therapeutic regimen, deceasing rectal cancer mortality have been observed [5]. Anti-EGFR (epidermal growth factor receptor) drug is proven effective to rectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, CT parameters, especially SRV, have been assessed to predict KRAS mutation. Lymph node enlargement (LNE), distant metastasis, enhanced pattern, CT ratio and the length of tumor were supposed to imply the different invasive behaviors of rectal carcinoma [5]. And the correlation between pathological ndings and KRAS status has also been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have mainly focused on the relationship between the tumor metabolism evaluated by positron emission tomography/ computed tomography with 18F‐fluorodeoxyglucose (18F‐FDG PET/CT) and genetic mutations in CRC or rectal cancer; however, with conflicting results . Magnetic resonance imaging (MRI) based on morphologic features and quantitative parameters derived by using diffusion‐weighted imaging (DWI) may help predict mutation status of various tumors . However, conventional DWI using a monoexponential model has the limitation of only assessing the Gaussian water diffusion behavior.…”
mentioning
confidence: 99%
“…[12][13][14][15][16] Magnetic resonance imaging (MRI) based on morphologic features and quantitative parameters derived by using diffusion-weighted imaging (DWI) may help predict mutation status of various tumors. [17][18][19][20] However, conventional DWI using a monoexponential model has the limitation of only assessing the Gaussian water diffusion behavior. Diffusion kurtosis imaging (DKI), an advanced non-Gaussian DWI model, can provide more precise information in terms of the heterogeneity and irregularity of tissue components.…”
mentioning
confidence: 99%